Can swimmers with Down Syndrome follow a visual pacer in an incremental protocol pacing - Querido, A.; Corredeira, R.; Vilas-Boas, J. P.; Daly, D.; Fernandes, R. J. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Down syndrome is one of the most common genetic causes of intellectual disability (1). This condition occurs when there is an extra copy of the 21st chromosome. This gene over-expression leads to a highly complex and variable phenotype, in which physical and cognitive development are significantly altered (2). In total, there are over 80 clinical features occurring more frequently among individuals with Down syndrome than the population at large (3). Despite this, there is a very pronounced lack of knowledge on factors leading to sport success in these individuals, particularly in swimming. The well known positive relationship between physical activity and health may be even more important for individuals with disabilities. For these individuals physical activity can help them to improve ability to perform daily life activities, a critical factor in maintaining independence (4, 5, 6). Nevertheless, few investigations report findings in trained individuals with intellectual disabilities (7), even more in the case of a specific disability, such as Down syndrome. Furthermore, too often, one is left with the belief that the nature of the intellectual disability renders it impossible for a person to engage in the level of training or mental preparation required for high level competition (7). The ability to follow a race strategy might be a potential problem for persons with an intellectual disability. This is important to optimal performance. Little is known about this ability. In a previous study on race analysis for swimmers with Down syndrome (8), it was observed that for the 100 m freestyle these swimmers presented significant differences in speed and stroke rate from the 1st to the 2nd laps, and from the 2nd to the 3rd laps. Especially for stroke rate, there was a marked decrease on the 2nd lap, and a little less decrease on the 3rd lap. This could mean that swimmers with Down syndrome have trouble on pacing well in the race. The aim of this study was to verify if swimmers with DS are able to follow a visual pacer, and maintain velocity when swimming without the pacer.